Anti-atrial Fibrillation Effects of Pulmonary Vein Isolation With or Without Ablation Gaps: A Computational Modeling Study - Jin, Ze; Hwang, Inseok; Lim, Byounghyun; Kwon, Oh-Seok; Park, Je-Wook; Yu, Hee-Tae; Kim, Tae-Hoon; Joung, Boyoung; Lee, Moon-Hyoung; Pak, Hui-Nam (Frontiers in Physiology, 2022)
Background Although pulmonary vein isolation (PVI) gaps contribute to recurrence after atrial fibrillation (AF) catheter ablation, the mechanism is unclear. We used realistic computational human AF modeling to explore the AF wave-dynamic changes of PVI with gaps (PVI-gaps). Methods We included 40 patients (80% male, 61.0±9.8 years old, 92.5% persistent AF) who underwent AF catheter ablation to develop our realistic computational AF model. We compared the effects of a complete PVI (CPVI) and PVI-gap (2-mm x 4) on the AF wave-dynamics by evaluating the dominant frequency (DF), spatial change of DF, maximal slope of the action potential duration restitution curve (Smax), and AF defragmentation rate (termination or change to atrial tachycardia), and tested the effects of additional virtual interventions and flecainide on ongoing AF with PVI-gaps. Results Compared with the baseline AF, CPVIs significantly reduced extra-PV DFs (p<0.001), but PVI-gaps did not. COV-DFs were greater after CPVIs than PVI-gaps (p<0.001). Neither CPVIs nor PVI-gaps changed the mean Smax. CPVIs resulted in higher AF defragmentation rates (80%) than PVI-gaps (12.5%, p<0.001). In ongoing AF after PVI-gaps, the AF defragmentation rates after a wave-breaking gap ablation, extra-PV DF ablation, or flecainide were 60.0%, 34.3%, and 25.7%, respectively (p=0.010). Conclusions CPVIs effectively reduced the DF, increased its spatial heterogeneity in extra-PV areas, and offered better anti-AF effects than extra-PV DF ablation or additional flecainide in PVI-gap conditions.